Mechanisms of Intranasal Deferoxamine in Neurodegenerative and Neurovascular Disease - Jacob Kosyakovsky; Jared M. Fine; William H. Frey; Leah R. Hanson (Pharmaceuticals, 2021)
Identifying disease-modifying therapies for neurological diseases remains one of the greatest gaps in modern medicine. Herein, we present the rationale for intranasal (IN) delivery of deferoxamine (DFO), a high-affinity iron chelator, as a treatment for neurodegenerative and neurovascular disease with a focus on its novel mechanisms. Brain iron dyshomeostasis with iron accumulation is a known feature of brain aging and is implicated in the pathogenesis of a number of neurological diseases. A substantial body of preclinical evidence and early clinical data has demonstrated that IN DFO and other iron chelators have strong disease-modifying impacts in Alzheimer’s disease (AD), Parkinson’s disease (PD), ischemic stroke, and intracranial hemorrhage (ICH). Acting by the disease-nonspecific pathway of iron chelation, DFO targets each of these complex diseases via multifactorial mechanisms. Accumulating lines of evidence suggest further mechanisms by which IN DFO may also be beneficial in cognitive aging, multiple sclerosis, traumatic brain injury, other neurodegenerative diseases, and vascular dementia. Considering its known safety profile, targeted delivery method, robust preclinical efficacy, multiple mechanisms, and potential applicability across many neurological diseases, the case for further development of IN DFO is considerable.